Acute and Chronic anti-hyperglycemic effect of Prosopis ruscifolia extract in Normoglycemic and Alloxan-Induced Hyperglycemic Rats - Miguel A. Campuzano-Bublitz, Derlis A. Ibarrola, María C. Hellión-Ibarrola, Julio H. Dölz, María L. Kennedy (Journal of Applied Pharmaceutical Science, 2016)
Prosopis ruscifolia, vinal, is used to treat diabetes. This work aims to study the influence of the hydro-alcoholic extract of this plant on alloxan induced diabetic rats. Hydroalcoholic extract from aerial parts of Prosopis ruscifolia Griseb. (Fabaceae) was prepared (Pr) and the safety was assessed to determine the acute toxicity in mice. The hypoglycemic activity of the extract was evaluated in normo- and hyperglycemic rats. Hyperglycemia was induced by intravenous administration of alloxan monohydrate (32 mg/Kg body weight). Rats with blood glucose level higher than 200 mg/dL were used for the experiment. The animals were assigned to different groups and treated with a single dose of solvent (water, p.o.), Pr (100 mg/Kg, p.o.), tolbutamide (100 mg/Kg, p.o.) or insulin (5 IU/kg, i.p.); Pr extract was also administered to normoglycemic rats (100 mg/kg, p.o.). Fasted blood glucose level was measured at times 0, 1, 2, 4 and 24 h after treatment, in the acute test, and at days 0, 14, 21 and 28, in the chronic study. No evidence of acute toxicity in mice was observed. The results show that Pr extract significantly reduces blood glucose level in hyperglycemic rats (p < 0.01) 24 h after administration of a single oral dose of 100 mg/Kg. Treatment with Pr during 28 days showed a reduction in blood glucose level in experimentally hyperglycemic rats. Additionally, rats treated with the extract showed a reduced body weight gain. Prosopis ruscifolia hydroalcoholic extract showed low toxicity. After acute and chronic oral treatment was effective to reduce fasted blood glucose level, and the body weight gain was less after 28 days in the treated group.
Keywords: Prosopis ruscifolia, hypoglycemic activity, rats, alloxan induced hyperglycemia.